2011
DOI: 10.1177/0003122411401250
|View full text |Cite
|
Sign up to set email alerts
|

The Initial Assignment Effect

Abstract: One of the great paradoxes of inequality in organizations is that even when organizations introduce new programs such as work-family programs designed to help employees in traditionally disadvantaged groups succeed, employees who use the programs often suffer negative career consequences. This study helps to fill a significant gap in the literature by investigating how local employer practices can enable employees to successfully use programs designed to benefit them. Using a research approach that controls fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…That said, the new ties that employees create on the job may have additional lasting effects. Briscoe and Kellogg (), for instance, argue that workers assigned to powerful supervisors achieve higher salaries and are more likely to be retained, as employees' “initial assignment” may confer access to superior networking opportunities via their managers.…”
Section: Network and Individual‐level Employment Outcomesmentioning
confidence: 99%
“…That said, the new ties that employees create on the job may have additional lasting effects. Briscoe and Kellogg (), for instance, argue that workers assigned to powerful supervisors achieve higher salaries and are more likely to be retained, as employees' “initial assignment” may confer access to superior networking opportunities via their managers.…”
Section: Network and Individual‐level Employment Outcomesmentioning
confidence: 99%
“…Similarly, the fear of negative career consequences when utilizing family-friendly arrangements is closely linked to notions of the ideal worker (Acker, 1990), who is engaged in full-time paid employment while unencumbered by family demands or other commitments outside the workplace. Individual consequences of the (non) utilization of family-friendly arrangements for careers, couples and children vary widely when we consider different indicators of work-family interaction (e.g., enrichment, harmony, conflict, spillover, guilt, life and marital satisfaction, e.g., Eby, Casper, Lockwood, Bordeaux, & Brinley, 2005;Ford, Heinen, & Langkamer, 2007), objective indicators of career success (e.g., salary growth and career advancement, e.g., Briscoe & Kellogg, 2011), subjective indicators of work and career success (e.g., job and career satisfaction, person-organization fit, engagement or burnout, turnover, e.g., Eby et al, 2005), and children's wellbeing, achievement, and development (e.g., Goldberg, Prause, Lucas-Thompson, & Himsel, 2008). Negative outcomes of combining career and care over time may reinforce traditional (and gendered) notions of the ideal parent and the ideal worker, whereas positive outcomes may challenge and ultimately change such beliefs.…”
mentioning
confidence: 99%
“…However, quantitative studies from other European countries have found no statistically relevant relationship between perceptions of supervisor support and fathers' or mothers' use of parenting leave (Haas et al, 2002, for Sweden;Samtleben et al, 2019, for Germany;van Breeschoten et al, 2019, for nine European countries). Interestingly, however, supervisor support has been shown to play an important role in protecting employees, and specifically mothers, from potential negative career consequences of using family policies (see also Briscoe & Kellogg, 2011 for the US; Samtleben et al, 2019 for Germany). Thus, while it is not entirely clear to what extent manager support affects mothers' and fathers' decisions about parenting leave, the social support provided by managers as well as their own use of parenting leave can undoubtedly help to promote the general acceptance of parenting leave within organizations.…”
Section: Peer Behavior and Managerial Supportmentioning
confidence: 99%